Multilevel collaborative governance in territories seeking decentralization: an innovative experience for sustainability in the Los Lagos Region, Chile - Rivera Mercado, Claudio; Zahn Muñoz, Cristian; Díaz López, Guillermo; Gallardo Gallardo, Juan; Braüning Wistuba, Mirna; Garrido Álvarez, Oscar (Estado, Gobierno y Gestión Pública, 2024)
Multi-level collaborative governance, a way of sharing power and managing resources, creates an opportunity for regions. This article systematizes and analyzes an innovative experience in Los Lagos Region, Chile where collaborative governance enabled the articulation of public and private actors around common sustainability and inclusion goals. The study analyzes the theoretical implications for governance studies and contributes to empirical studies about governance, identifying constraints and enablers in the process. The results suggest that collaborative governance processes are possible when innovative political leadership and professional support achieve high legitimacy. The case provides important lessons for replicable experiences of multilevel collaborative governance.